Peningkatan Hasil Pembelajaran Tematik Terpadu dengan Model Cooperative Tipe make a Match di Kelas IV SD N 015 Simangambat - Fadhilah Muthmainnah; Desyandri Desyandri (Institut Agama Islam Negeri Padangsidimpuan, 2022)
This research is a classroom action research (CAR). The approaches used are qualitative and quantitative approaches. It was carried out in two cycles, namely the first cycle consisting of 2 meetings, and the second cycle consisting of 1 meeting. Each cycle includes four stages, namely planning, implementation, observation, and reflection. The subjects of this study were teachers and students with a total of 20 students. The data source is the process and results of implementing integrated thematic learning with a make a match type cooperative model. The technique used is observation, tests, and non-tests that are observed are lesson plans, teacher aspects and student aspects. The results showed an increase in: a) RPP cycle I obtained an average of 78.75% with good qualifications (B), and cycle II obtained an average of 95% with very good qualifications (SB). b) Implementation in the teacher aspect of cycle I obtained an average of 78,08% good qualifications (B), and cycle II obtained an average of 96.8% very good qualifications (SB). c) Assessment of students in improving learning outcomes in the first cycle obtained an average of 79.65%, and the second cycle with an average of 93.75%. Based on these results, it can be concluded that the cooperative model of the make a match type can improve student learning outcomes in integrated thematic learning